Cannabinoid‐1 receptor deletion in podocytes mitigates both glomerular and tubular dysfunction in a mouse model of diabetic nephropathy. Issue 3 (3rd December 2017) - Jourdan, Tony; Park, Joshua K.; Varga, Zoltán V.; Pálóczi, János; Coffey, Nathan J.; Rosenberg, Avi Z.; Godlewski, Grzegorz; Cinar, Resat; Mackie, Ken; Pacher, Pal; Kunos, George
Abstract : Aims: To determine the specific role of podocyte‐expressed cannabinoid‐1 receptor (CB1 R) in the development of diabetic nephropathy (DN), relative to CB1 R in other renal cell types. Material and methods: We developed a mouse model with a podocyte‐specific deletion of CB1 R (pCB1Rko) and challenged this model with streptozotocin (STZ)‐induced type‐1 DN. We also assessed the podocyte response to high glucose in vitro and its effects on CB1 R activation. Results: High glucose exposure for 48 hours led to an increase in CB1 R gene expression ( CNR1 ) and endocannabinoid production in cultured human podocytes. This was associated with podocyte injury, reflected by decreased podocin and nephrin expression. These changes could be prevented by Cnr1 ‐silencing, thus identifying CB1R as a key player in podocyte injury. After 12 weeks of chronic hyperglycaemia, STZ‐treated pCB1Rko mice showed elevated blood glucose similar to that of their wild‐type littermates. However, they displayed less albuminuria and less podocyte loss than STZ‐treated wild‐type mice. Unexpectedly, pCB1Rko mice also have milder tubular dysfunction, fibrosis and reduction of cortical microcirculation compared to wild‐type controls, which is mediated, in part, by podocyte‐derived endocannabinoids acting via CB1 R on proximal tubular cells. Conclusions: Activation of CB1 R in podocytes contributes to both glomerular and tubular dysfunction in type‐1 DN, which highlights the therapeutic potential of peripheral CB1 R blockade.